If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 9(x + -8) Reorder the terms: x = 9(-8 + x) x = (-8 * 9 + x * 9) x = (-72 + 9x) Solving x = -72 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. x + -9x = -72 + 9x + -9x Combine like terms: x + -9x = -8x -8x = -72 + 9x + -9x Combine like terms: 9x + -9x = 0 -8x = -72 + 0 -8x = -72 Divide each side by '-8'. x = 9 Simplifying x = 9
| 11x-7=-5x+9 | | 2x+6xz=a | | 3x+1.2= | | -5(6)(-1)(-1)= | | 7.5k=.75 | | 23000+130h=43000 | | 2x+5.2= | | 12x-2+18x+2=180 | | 40b+25=-95 | | 3p=5p-5 | | x+4+1+7=3x | | -7x+1+5x=-21 | | 2x^2+16x-18=0 | | 9(x+2)-6=3x-7+4x | | 7(3k+3)-3=165 | | 9-3x=7x-2(2-x) | | 4q=36-14q | | 2-c=12c | | X=4y-16 | | -15-3=4x-2x | | 2(x-1)-14=6 | | 5(1+2n)+6(n-3)=8n-5n | | (3x+8)=(5x-12) | | 7-3x=7+2(6-x) | | -5(3-7n)=90 | | 8x-12+x=-4x-3 | | -11+-16= | | 2z-5=3z-4 | | -14+15=m-7 | | -6(x+1)=6-5x | | 36+36-18= | | ln(1-3x)+C=ln(x)+C |